Power electronics handbook devices, circuits, and applications - Rashid, Muhammad H. (Muhammad Harunur), 1945- (Burlington, MA : Butterworth-Heinemann, 2011)
"Designed to appeal to a new generation of engineering professionals, Power Electronics Handbook, 3rd Edition features four new chapters covering renewable energy, energy transmission, energy storage, as well as an introduction to Distributed and Cogeneration (DCG) technology, including gas turbines, gensets, microturbines, wind turbines, variable speed generators, photovoltaics and fuel cells, has been gaining momentum for quite some time now.smart grid technology. With this book readers should be able to provide technical design leadership on assigned power electronics design projects and lead the design from the concept to production involving significant scope and complexity"--
Preface, Chapter 1 -- Introduction Chapter 2 -- The power diode Chapter 3 -- Power bipolar transistors Chapter 4 -- The power MOSFET Chapter 5 -- Insulated gate bipolar transistor Chapter 6 -- Thyristors Chapter 7 -- Gate turn-off thyristors Chapter 8 -- MOS Controlled Thyristors (MCTs), Chapter 9 -- Static induction devices Chapter 10 -- Diode rectifiers Chapter 11 -- Single-phase controlled rectifiers Chapter 12 -- Three-Phase controlled rectifiers Chapter 13 -- DC-DC converters Chapter 14 -- DC/DC conversion technique and twelve series luo-converters Chapter 15 -- Inverters Chapter 16 -- Resonant and soft-switching converters Chapter 17 -- Multilevel power converters Chapter 18 -- AC-AC converters Chapter 19 -- Power factor correction circuits Chapter 20 -- Gate drive circuitry for power converters Chapter 21 -- Power electronics in capacitor charging applications Chapter 22 -- Electronic ballasts, Chapter 23 -- Power supplies, Chapter 24 -- Uninterruptible power supplies, Chapter 25 -- Automotive applications of power electronics Chapter 26 -- Solar power conversion, Chapter 27 -- Power electronics for renewable energy sources, Chapter 28 -- Fuel-cell power electronics for distributed generation, Chapter 29 -- Wind turbine applications Chapter 30 -- HVDC transmission Chapter 31 -- Flexible AC transmission systems, Chapter 32 -- Drives types and Specifications, Chapter 33 -- Motor drives, Chapter 34 -- Control methods for switching power converters Chapter 35 -- Fuzzy logic in electric drives Chapter 36 -- Artificial neural network applications in power electronics and electrical drives Chapter 37 -- DSP-based control of variable speed drives Chapter 38 -- Power quality Chapter 39 -- Active filters Chapter 40 -- EMI Effects of power converters, Chapter 41 -- Computer simulation of power electronics and motor drives Chapter 42 -- Packaging and smart power systems Chapter 43-Renewable Energy Sources Chapter 44- Renewable Energy Storage Chapter 45- Renewable Electric Power Transmission Chapter 46- Distributed and Cogeneration.
Includes bibliographical references.
Keywords: Power electronics -- Encyclopedias; Electronic books